Framing Realitas Sosial dalam Proses Produksi Program "Cerita Muslimah" MQTV untuk Syiar Islam - Nazwa Sabila Febiana; Parihat Kamil; Asep Ahmad Siddiq (Jurnal Riset Komunikasi Penyiaran Islam, 2026)
Abstract. The development of television-based da‘wah media presents ethical challenges in packaging sensitive social issues so that they do not shift toward sensationalism while remaining capable of attracting audience attention. Cerita Muslimah, a program broadcast on MQTV, represents a form of da‘wah programming that presents real-life stories of women through a consultative format, thereby shaping audience interpretations of social and religious realities. This study aims to analyze the process of framing social reality in the production of the Cerita Muslimah program, including the selection of issues and da‘wah values, the application of framing strategies during the pre-production, production, and post-production stages, the construction of da‘wah values, as well as the supporting and inhibiting factors in the production process. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using Robert N. Entman’s framing model supported by Berger and Luckmann’s theory of social construction. The findings indicate that da‘wah framing is applied consistently from the planning stage through post-production, enabling sensitive issues to be presented in a reflective and solution-oriented manner while maintaining the integrity of Islamic da‘wah values. Abstrak. Perkembangan media dakwah melalui televisi menghadirkan tantangan etis dalam mengemas isu sosial yang sensitif agar tidak bergeser ke arah sensasional, namun tetap mampu menarik perhatian audiens. Program Cerita Muslimah di MQTV menjadi salah satu contoh tayangan dakwah yang mengangkat kisah nyata perempuan melalui format konsultatif, sehingga berpotensi membentuk pemaknaan audiens terhadap realitas sosial dan keagamaan. Penelitian ini bertujuan untuk menganalisis proses framing realitas sosial dalam produksi program Cerita Muslimah, meliputi pemilihan isu dan nilai dakwah, penerapan strategi framing pada tahap pra-produksi, produksi, dan pascaproduksi, konstruksi nilai dakwah, serta faktor pendukung dan penghambat dalam proses produksi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis menggunakan model framing Robert N. Entman dengan dukungan teori konstruksi sosial Berger dan Luckmann. Hasil penelitian menunjukkan bahwa framing dakwah diterapkan secara konsisten sejak tahap perencanaan hingga pascaproduksi, sehingga isu-isu sensitif disajikan secara reflektif, solutif, dan tetap menjaga integritas nilai dakwah Islam.